Factores de riesgo su influencia en la rinofaringitis en niños menores de 10 años de la ciudadela Lupita Cantón Baba. Los Ríos. Septiembre 2017 - febrero - Muñoz Chiriguay, Astrid Carolina (2018)
Rhinopharyngitis is a viral infection of the upper respiratory tract, more common than any other respiratory tract infection. Most adults suffer two to four colds per year: the average schoolchild can experience up to ten per year. This entity usually begins with a sensation of dryness and congestion that mainly affects the nasopharynx, accompanied by excessive production of nasal secretions and tearing or watery eyes. Usually, the secretions remain clear and watery. The mucous membranes of the upper respiratory tract become red and swollen and are covered by secretions. The involvement of the pharynx and larynx causes sore throat and hoarseness. This research project was developed with the aim of discovering the risk factors that cause rhinopharyngitis in children under 10 years of age, for which the general objective was to determine the risk factors that influence rhinopharyngitis in children under 10 years of the citadel lupita canton baba. The rivers. September 2017 - February 2018 for the development of this research a descriptive methodology was used: because it consists of discovering the current state of cases, explaining the qualities, properties or circumstances not only by their attributes but rather giving a complete idea of the context interpreting in ordered form the information according to each study variable. Explicative: it allowed us to discover the causes, consequences and effects of the phenomena investigated, obtaining favorable results in the project. It was concluded that in order to prevent the proliferation of rhinopharyngitis in children under 10 years, the risk factors that cause it must be reduced, as well as the knowledge of the risk factors and how to treat the first symptoms of rhinopharyngitis is very important to stop the evolution of respiratory infection.